2019
DOI: 10.3390/en12214068
|View full text |Cite
|
Sign up to set email alerts
|

Suppression Effects of Hydroxy Acid Modified Montmorillonite Powders on Methane Explosions

Abstract: In this paper, montmorillonite inhibitors modified with polyhydroxy functional groups by gluconic acid (GA) were successfully prepared. The particle size distribution, composition, surface functional groups, and pyrolysis characteristics of the pure montmorillonite powders (Mt) and the gluconic acid modified powders (G-Mt) were analyzed by using a laser particle analyzer, X-ray diffraction (XRD), Fourier transform infrared (FTIR) and thermogravimetry-differential scanning calorimetry (TG-DSC), respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…This could be due to the residue of alumina and water vapour from the ATH, which prevents the MMT barrier layer formation when the composite decomposition occurs [62]. Another factor that may also occur is the hydroxyl from MMT which is released then reacts with oxygen and becomes reactive [70]. This is contrary to the purpose of MMT as a flame retardant, which is to switch functions to accelerate the decomposition of polyester [58].…”
Section: The Rate Of Linear Burning (Rob) Of the Compositesmentioning
confidence: 99%
“…This could be due to the residue of alumina and water vapour from the ATH, which prevents the MMT barrier layer formation when the composite decomposition occurs [62]. Another factor that may also occur is the hydroxyl from MMT which is released then reacts with oxygen and becomes reactive [70]. This is contrary to the purpose of MMT as a flame retardant, which is to switch functions to accelerate the decomposition of polyester [58].…”
Section: The Rate Of Linear Burning (Rob) Of the Compositesmentioning
confidence: 99%
“…Among inert additives, CO 2 had the highest efficiency, followed by N 2 , Ar, and He. On the other hand, Song et al [13][14][15] studied the inhibition effect of inert dust and solid particle inhibitors [16] on gas explosions, finding that particle size has a great influence on inert rock dust to inhibit gas explosions. In addition, Chen et al [17,18] studied metal foam and found that it can reduce the overpressure generated, but it has little effect on the flame tip speed and shape.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have made considerable progress in the field of gas explosion suppression technology. A large number of studies have focused on the use of inert gas [7][8][9][10], ultrafine water mist [11,12], and powder inhibitors [13][14][15] to suppress and mitigate gas explosions. Previous work explored the impact of various materials on the suppression of methane explosions.…”
Section: Introductionmentioning
confidence: 99%